Perbedaan Kekuatan Fleksural Plat Ortodonti Resin Akrilik Self-Cure dengan Modifikasi Motif Bulat dan Persegi - Nadya Ayustia; Setiadi Warata Logamarta; Dian Noviyanti Agus Imam (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2020)
Orthodontic baseplate generally don’t have any motive. However, these baseplate has a less attractive esthetic value especially for the treatment of children and teenagers. Orthodontic baseplate that modified by motive are currently being developed to motivate the patient to be more cooperative in using these appliance so it can increase the success of the treatment. Motive that generally applied were round and square. Aim, to analyze the flexural strength difference of self-cure acrylic resin orthodontic baseplate with spray-on method with or without modified by round and square motive. 27 plates (n=9) of self-cured acrylic resin with size 65x10x2,5 mm were divided into 3 groups. Group I (orthodontic baseplate modified by round motive), group II (orthodontic baseplate modified by square motive), and group III (orthodontic baseplate without giving any motive) as control group. Flexural strength test was carried out using Universal Testing Machine. Mean value of all groups were 46,06 MPa (Group I), 35,59 MPa (Grup II), and 77,11 MPa (Group III). Data analyzed using One-Way ANOVA and Post-Hoc LSD. Results, there were significant differences in the flexural strength among all groups (p<0,05). Conclusion, modification by giving round and square motive can decrease the flexural strength of self-cure acrylic resin orthodontic baseplate. Orthodontic baseplate modified by round motive was far superior than square motive.